Serum immunoglobulin G antibody titer to Fusobacterium nucleatum is associated with unfavorable outcome after stroke. (24th March 2020) - Nishi, H; Hosomi, N; Ohta, K; Aoki, S; Nakamori, M; Nezu, T; Shigeishi, H; Shintani, T; Obayashi, T; Ishikawa, K; Kinoshita, N; Shiga, Y; et al.
Summary: Stroke can be a cause of death, while in non-fatal cases it is a common cause of various disabilities resulting from associated brain damage. However, whether a specific periodontal pathogen is associated with increased risk of unfavorable outcome after stroke remains unknown. We examined risk factors for unfavorable outcome following stroke occurrence, including serum antibody titers to periodontal pathogens. The enrolled cohort included 534 patients who had experienced an acute stroke, who were divided into favorable ( n = 337) and unfavorable ( n = 197) outcome groups according to modified ranking scale (mRS) score determined at 3 months after onset (favorable = score 0 or 1; unfavorable = score 2–6). The associations of risk factors with unfavorable outcome, including serum titers of IgG antibodies to 16 periodontal pathogens, were examined. Logistic regression analysis showed that the initial National Institutes of Health stroke scale score [odds ratio (OR) = 1·24, 95% confidence interval (CI) = 1·18–1·31, P < 0·001] and C-reactive protein (OR = 1·29, 95% CI = 1·10–1·51, P = 0·002) were independently associated with unfavorable outcome after stroke. Following adjustment with those, detection of the antibody for Fusobacterium nucleatum ATCC 10953 in serum remained an independent predictor of unfavorable outcome (OR = 3·12, 95% CI = 1·55–6·29, P = 0·002). Determination of the antibody titer to F. nucleatum ATCC 10953 in serum may be useful as a predictor of unfavorable outcome after stroke. Graphical Abstract: We examined risk factors for unfavorable outcome following stroke occurrence including serum antibody titers to periodontal pathogens. The enrolled cohort included 534 patients who had experienced an acute stroke, who were divided into favorable (n = 337) and unfavorable (n = 197) outcome groups according to modified ranking scale (mRS) score determined at 3 months after onset. Logistic regression analysis showed that detection of the antibody for F. nucleatum ATCC10953 in serum were independently associated with unfavorable outcome after stroke.